Cardiovascular diseases and the work environment. A critical review of the epidemiologic literature on nonchemical factors. - Kristensen, Tage S (Scandinavian Journal of Work, Environment & Health, 1989)
This is the first of two articles reviewing the epidemiologic research on cardiovascular diseases (CVD) and the work environment. It deals with a number of nonchemical factors, ie, physical inactivity at work, stressors at work, shift work, noise, cold, heat, and electromagnetic fields and waves. First the methodological quality of each of the empirical studies is assessed on the basis of epidemiologic criteria. Then the research literature on each of the aforementioned factors of the work environment is evaluated. It is concluded that the hypothesis of a causal relationship between physical inactivity at work and risk of CVD is substantially supported by the literature. As regards work stressors and shift work, several good studies have been published during the last 10 years strongly suggesting a causal relationship. Other studies have shown a relationship between noise and elevated blood pressure, but the quality of this literature is low. Heat and cold appear to have an acute effect on the incidence of CVD, but the possible chronic effect has seldom been investigated. Concerning electromagnetic fields and waves, it is concluded that more research is needed. The study of CVD and work ought to play a bigger role in research in the fields of occupational medicine and cardiovascular epidemiology in the future.
Keywords: cardiovascular disease; CVD; electromagnetic fields; electromagnetic waves; epidemiologic literature; epidemiology; heat; hypertension; ischemic heart disease; noise; nonchemical factor; occupation; physical inactivity; review; shift work; stressor at work; work environment